2020
DOI: 10.1039/d0ta06020h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding additive controlled lithium morphology in lithium metal batteries

Abstract: Investigation of the mechanisms underlying control of electrodeposited lithium metal morphology using electrolyte additives in lithium metal batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 49 publications
6
51
5
Order By: Relevance
“…[14][15][16] These studies showed that the crystallographic features of a metal deposit formed at the interface can serve as a sensitive indicator of the electrodeposition quality, including the geometry of the crystallite building blocks and the orientational order parameter with respect to the electrode surface. [9] A universal rule, independently established in different metal systems, e.g., Zn [14,17] and Li, [8,18] is that stable plating/stripping can be achieved when the deposits exhibit a strong crystallographic texture (e.g., as produced by aligning the close-packed crystal plane with the substrate). Multiple approaches for obtaining such textured metal deposits have been proposed, including heteroepitaxy, convective flow, electrolyte additive, and so on; it is remarkable that all appear to be successful in controlling the metal electrodeposit morphology during the plating process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] These studies showed that the crystallographic features of a metal deposit formed at the interface can serve as a sensitive indicator of the electrodeposition quality, including the geometry of the crystallite building blocks and the orientational order parameter with respect to the electrode surface. [9] A universal rule, independently established in different metal systems, e.g., Zn [14,17] and Li, [8,18] is that stable plating/stripping can be achieved when the deposits exhibit a strong crystallographic texture (e.g., as produced by aligning the close-packed crystal plane with the substrate). Multiple approaches for obtaining such textured metal deposits have been proposed, including heteroepitaxy, convective flow, electrolyte additive, and so on; it is remarkable that all appear to be successful in controlling the metal electrodeposit morphology during the plating process.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple approaches for obtaining such textured metal deposits have been proposed, including heteroepitaxy, convective flow, electrolyte additive, and so on; it is remarkable that all appear to be successful in controlling the metal electrodeposit morphology during the plating process. [10] Noticeable is that these prior studies focus on metal deposition on substrates that are of chemistries different from the metal-such as Li on Cu, [18] Zn on carbon, [14] Zn on stainless steel, [19] etc., whereas in a deployable battery setup, the working anode is in the form of a thin metal foil pre-stored in the battery. The amount of the pre-stored metal typically exceeds-by at least one order of magnitude in most state-ofthe-art studies-the amount that is plated/stripped in each battery cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In general, ether electrolytes offer an electrochemical window with a relatively low upper limit, which has restricted their application in high-voltage batteries [32]. However, carbonate electrolytes, such as EC and DMC, are widely used in high-voltage batteries owing to their wide electrochemical windows [12][13][14][34][35][36][37]. Consequently, the commercial carbonatebased electrolyte cells exhibited better ICE at high voltage operation over 4 V compared to the ether based electrolyte due to ether solvent oxidation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the high cost, constant dendritic Li growth on the copper (Cu) current collector surface, and low coulombic efficiency (CE) associated with Li-metal anode result in poor cycle stability and safety hazards; therefore, these issues should be resolved for facilitating the practical applications of Li-metal anode. Efforts to address these challenges include the use of artificial solid electrolyte interphases (SEIs) [4], three-dimensional (3D) hosts [5][6][7][8][9][10], interlayers between Li and the separator [11], electrolyte additives [12][13][14][15][16][17], highly concentrated electrolytes [3,13], and solidstate batteries (SSBs) [1,3,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, uniform and lateral growth of the lithium metal deposits is realized until they bump into one another, after which the deposits are restricted to growing vertically. [39] The resulting highly ordered columnar structure with low tortuosity can further regulate the following Li plating/stripping processes during cycling and maintain the bulk Li with a continuous electron conducting pathway. [40] Full cells were assembled with LFP cathodes and VG-GP or Au-VG-GP-5 plated with 5 mAh cm À2 Li as the anodes.…”
Section: Resultsmentioning
confidence: 99%